The Effect Of Financial Literacy, Overconfidence, And Risk Tolerance On Investment Decision - Nur Yulianis; Erna Sulistyowati (Journal of Economics, Business, and Government Challenges, 2021)
This study aims to test and prove whether financial literacy, overconfidence, andrisk tolerance affect investment decisions. The sample in this study were 100respondents who met the criteria (namely: living in Sidoarjo, aged 20-24 years,owning pure gold as an investment instrument, and making purchases/investmentsat least once in the last year). This study used multiple linear regression analysis.As a result, it is known that the variables of financial literacy and overconfidencehave a significant effect on investment decisions. Meanwhile, the risk tolerancevariable has not a significant effect on investment decisions.